Factors Affecting the Ability of Local People to Participate in Community-Based Tourism in the Non Nuoc Cao Bang UNESCO Global Geopark Viet Nam - Cao Thi Thanh Phuong; Tran Chi Thien; Le Ngoc Nuong (Celebes Scholar pg, 2022)
Cao Bang province has great potential for tourism development in general and community tourism in particular thanks to its wealth of geological, geomorphological, biodiversity, environmental and cultural heritages. unique culture and humanity. Since UNESCO recognized Non Nuoc Cao Bang Global Geopark in 2018, tourism in the province has made great progress. However, CBT here has not yet developed strongly due to many barriers. Summarizing the opinions of 250 people from 06 CBT villages in the province and the comments of the Standing Committee of 6 Commune People's Committees with CBT villages will see the factors affecting the decision to participate in CBT development of households. indigenous people. Using exploratory factor analysis and multivariate regression methods with interview information from 250 people, it shows the influencing factors and their importance in influencing the decision to participate. CBT of households. In descending order of importance, these factors are arranged in the following order: economic benefits of households when participating in CBT, support policies of local authorities, support from businesses and non-governmental organizations government, local resources, social capital and the conditions of natural, material, financial, and labor resources of households. Impacting on these influencing factors is the solution to promote CBT in the province.